Experimental investigations and comparison of energy and exergy efficiencies of the box type and parabolic solar cooker - Rathore N.; Shukla S.K. (My University, 2025)
In this paper two different types of solar cookers namely a flat plate box type solar cooker (SBC) and a parabolic solar cooker (SPC) are investigated experimentally. Experiments were done at roof top of Renewable Energy Lab, Department of Mechanical Engineering, Institute of Technology, Banaras Hindu University (BHU), Varanasi, India during month of October and November 2008. For comparison, these two cookers were kept on a single platform to ensure the same solar conditions. The energy and exergy efficiencies of both the cookers were experimentally evaluated. The experimental time period was from 09:00 to 15:00 solar time. During this period, it was found that the daily average temperature of water in the SPC was 333 K and for SBC was 326 K and the daily average difference between the temperature of water in the cooking pot and the ambient air temperature was 31.6 K for SPC and 26.4 K for SBC. The energy output of the SPC varied between 0.65 to 39.3 W and 7.44 to 33.49 W for SBC, whereas its exergy output was in the range of 0.92 to 2.58 W for SPC and for SBC it varies from 0.65 to 1.45 W. The energy efficiency of the SPC varied from 0.42% to 5.27% and for the SBC it varies from 4.7% to 29.81%. Copyright © 2009 by ASME.